A Research of Flavonoids in Inflammation: Exploring Their Role in Modulating Pro-Inflammatory Pathways - Mishra, Pratiksha; Sharma, Vikas Kumar (Journal of Neonatal Surgery, 2025)
The objective of this study was to develop and evaluate the in-vitro and in-vivo efficacy of Citrus limon peel extract loaded silver Nano gel for the treatment of inflammation. To achieve this, the alcoholic extract of Citrus limon peel was first screened for the presence of phytochemical constituents. A silver Nano gel was then developed using the Citrus limon peel extract, which was subsequently evaluated for its anti-inflammatory activity using in-vitro and in-vivo models. The use of Citrus limon peel extract loaded silver Nano gel aims to overcome the limitations of conventional formulations, such as poor absorption and bioavailability, limited ability to reach the target site, and expensive production and formulation processes. By developing a nanogel-based formulation, the study seeks to improve the delivery and efficacy of the Citrus limon peel extract. The potential benefits of this developed silver nanogel include improved anti-inflammatory activity, better penetration, and reduced costs, making it a promising treatment option for inflammation. By leveraging the therapeutic properties of Citrus limon peel extract and the advantages of Nano gel technology, this study aims to provide a novel and effective solution for the treatment of inflammation. Future Prospects: Citrus limon peel extract based silver Nano gel were successfully formulated and this could be a promising approach for treatment of inflammation.